2011
DOI: 10.1017/s1751731111000139
|View full text |Cite
|
Sign up to set email alerts
|

Consumer response to the possible use of a vaccine method to control boar taint v. physical piglet castration with anaesthesia: a quantitative study in four European countries

Abstract: In most European countries, male piglets being reared for meat are physically castrated without anaesthesia in order to avoid boar taint and to safeguard sensory meat quality. This method is increasingly criticised for its violation of piglet welfare. Alternative methods are being researched and castration with anaesthesia or analgesia and vaccination (immunisation) against gonadotropinreleasing hormone (using Improvac R , Pfizer GmbH) have been proposed as possible solutions. In addition to efficacy, the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 29 publications
5
39
0
2
Order By: Relevance
“…Even though 60% of the participants indicated prior knowledge about the castration of male piglets, we suggest that most consumers did not know that intact adult males may develop boar taint. Vanhonacker and Verbeke (2011) also reported a low awareness of any correlation between boar taint and castration of males in Germany. We have, therefore, come to the conclusion that the labelling information "young boar meat" did not trigger any expectations that could shift the acceptance.…”
Section: Effect Of Label Information On Meat Evaluation and Expected mentioning
confidence: 99%
“…Even though 60% of the participants indicated prior knowledge about the castration of male piglets, we suggest that most consumers did not know that intact adult males may develop boar taint. Vanhonacker and Verbeke (2011) also reported a low awareness of any correlation between boar taint and castration of males in Germany. We have, therefore, come to the conclusion that the labelling information "young boar meat" did not trigger any expectations that could shift the acceptance.…”
Section: Effect Of Label Information On Meat Evaluation and Expected mentioning
confidence: 99%
“…Most retailers do not accept pork from immunocastrated pigs being afraid for poor public acceptance. However, in the case of Belgium, the acceptance of immunocastration led to a better welfare-friendly image of the retailer and large scale surveys conducted in European countries, showed that over 60% of surveyed consumers informed about the issue preferred immunocastration to surgical castration with anaesthesia [33]. …”
Section: Discussion Of the Survey Resultsmentioning
confidence: 99%
“…Besides one study based on in-depth interviews (Ouedraogo et al, 2009) and one study using focus group discussions (Hennessy and Newbold, 2004), insights and conclusions are mostly based on quantitative data collection through cross-sectional surveys using large consumer samples. The majority of the available studies are single-country studies, for example Hennesy and Newbold Allison et al (2008) and Vanhonacker and Verbeke (2011) report findings from a cross-cultural comparison study including individual consumer data from Belgium, France, Germany and the Netherlands, while in the PIGCAS project information was gathered from consumer representatives from 24 European countries (Ouedraogo et al, 2009).…”
Section: Consumer Perception Of Alternativesmentioning
confidence: 99%
“…The expected reasons for public concern relate to the possible perception of a (false) link with hormone treatment and eventual harmful residues Prunier and Bonneau, 2006;, which is a very sensitive issue among European meat consumers (Verbeke et al, 2007). However, the majority of these studies report a higher degree of consumer acceptance of immunocastration compared to physical castration (Hennessy and Newbold 2004;Lagerkvist et al 2006;Allison et al 2008;Giffin et al 2008;Vanhonacker et al 2009;Vanhonacker and Verbeke 2011;Tuyttens et al, 2011), with the exception of the study by Huber-Eicher and in Switzerland and the study by Fredriksen et al (2010) in Norway. The latter study used the term "medical castration" (when referring to immocastration) and presented the use of anaesthesia as the standard procedure when applying physical castration.…”
Section: Consumer Perception Of Alternativesmentioning
confidence: 99%
See 1 more Smart Citation